2013
DOI: 10.1021/cs400332y
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Conversion of CO2 to CO Using Rhenium Bipyridine Platforms Containing Ancillary Phenyl or BODIPY Moieties

Abstract: Harnessing of solar energy to drive the reduction of carbon dioxide to fuels requires the development of efficient catalysts that absorb sunlight. In this work, we detail the synthesis, electrochemistry and photophysical properties of a set of homologous fac-ReI(CO)3 complexes containing either an ancillary phenyl (8) or BODIPY (12) substituent. These studies demonstrate that both the electronic properties of the rhenium center and BODIPY chromophore are maintained for these complexes. Photolysis studies demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 53 publications
1
35
0
1
Order By: Relevance
“…Since BODIPY 4751 and other polypyrrole derivatives 5255 can absorb light throughout the visible region we rationalized that [Re(BB2)(CO) 3 Cl] might support an improved photocatalysis with CO 2 using sunlight, as compared to fac -Re I (CO) 3 frameworks lacking indacene units. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Since BODIPY 4751 and other polypyrrole derivatives 5255 can absorb light throughout the visible region we rationalized that [Re(BB2)(CO) 3 Cl] might support an improved photocatalysis with CO 2 using sunlight, as compared to fac -Re I (CO) 3 frameworks lacking indacene units. 56 …”
Section: Resultsmentioning
confidence: 99%
“…Generally, if the ligand reduction waves of the Re(I) complex occur at potentials more positive than À1.1 V, the complex displays very little electrocatalytic activity for the electroreduction CO 2 [19,27]. Thus, the tptzH À ligand in the complex acts as electron storage and improves the performance of the complex for its catalytic activity [16]. For an investigation of the stability and activity of the dinuclear Re(I) complex, the peak current of the CO 2 reduction was followed over 50 cycles of CVs recorded in a potential range from 700 to À1500 mV at a scan rate of 100 mV s À1 in an electrolyte solution saturated with CO 2 in the presence of the Re(I) complex.…”
Section: Catalytic Activity Of the Complex As A Homogenous Catalystmentioning
confidence: 99%
“…In particular, rhenium and ruthenium complexes have been more attracted due to their efficacious catalytic properties. Since the Re(bpy) (CO) 3 Cl complex was originally reported by Lehn [13], many researchers have studied the electrocatalytic [14,15] and photocatalytic [16,17] properties of this complex and its analogs. Several Re complexes have high selectivity for the reduction of CO 2 in the presence of protons [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…38 Using Ru II −Re I binuclear complexes, Bian et al 40 reported TONs in CO of 50−100 after 9 h of irradiation (TOFs of 5.5−11.1 h −1 ). Andrade et al 13 However, at such a low concentration of catalyst, it is difficult to assess the nature of the active species (along this line, it should be noted that the concentration of CO produced slightly decreases when the catalyst concentration increases from 2 to 20 nM and then marginally increases (by a factor of 1.5) when the concentration is further increased by a factor of 10).…”
mentioning
confidence: 99%